Theory of Connectivity: Nature and Nurture of Cell Assemblies and Cognitive Computation - Li, Meng; Liu, Jun; Tsien, Joe Z. (Frontiers in Neural Circuits, 2016)
Richard Semon and Donald Hebb are among the firsts to put forth the notion of cell assembly – a group of coherently or sequentially-activated neurons– to represent percept, memory, or concept. Despite the rekindled interest in this age-old idea, the concept of cell assembly still remains ill-defined and its operational principle is poorly understood. What is the size of a cell assembly? How should a cell assembly be organized? What is the computational logic underlying Hebbian cell assemblies? How might Nature vs Nurture interact at the level of a cell assembly? In contrast to the widely assumed local randomness within the mature but naïve cell assembly, the recent Theory of Connectivity postulates that the brain consists of the developmentally pre-programmed cell assemblies known as the functional connectivity motif (FCM). Principal cells within such FCM is organized by the power-of-two-based mathematical principle that guides the construction of specific-to-general combinatorial connectivity patterns in neuronal circuits, giving rise to a full range of specific features, various relational patterns, and generalized knowledge. This pre-configured canonical computation is predicted to be evolutionarily conserved across many circuits, ranging from these encoding memory engrams and imagination to decision-making and motor control. Although the power-of-two-based wiring and computational logic places a mathematical boundary on an individual’s cognitive capacity, the fullest intellectual potential can be brought about by optimized nature and nurture. This theory may also open up a new avenue to examining how genetic mutations and various drugs might impair or enhance the computational logic of brain circuits.